Effects of method of harvest of Triticum aestivum L. on straw biomass and estimated accumulation of soil carbon. (6th September 2017) - Weiser, C.; Bischof, R.; Heß, H.
Summary: Climate change and increased extraction of agricultural residues for bioenergy can adversely affect soil fertility. A more accurate understanding of biomass that remains in or on arable soil is necessary to improve results of carbon (C) balances of cropped land. Mechanical and manual harvesting of winter wheat grain and material other than grain (MOG) were carried out at three field stations in Thuringia, Germany, in 2012 and 2013. We compared various methods of harvesting MOG, which resulted in different straw/grain ratios (SGR) and their effect on C balancing. For all experiments, the total biomass yield and SGR were larger for manual than mechanical harvesting. Substantial differences in SGR resulted for the various methods of mechanical MOG recovery. Surprisingly, methods of harvesting without biomass deposition to the soil surface cannot be regarded as more accurate in general than those with intermediate MOG deposition. Using these SGRs to determine the amount of MOG available for the maintenance of soil organic carbon (SOC) resulted in an underestimate of the actual biomass by up to 47%. For stubble heights of 5–15 cm, a mean of 8–22% of MOG remained in the field as stubble. Thus, the method of MOG assessment should be considered for SGR values used to calculate the C input as a model parameter. We demonstrated that SOC is underestimated by up to 24% when the simplified C turnover model CANDY Carbon Balance (CCB) is not parameterized correctly. Highlights: How do specific straw/grain ratios (SGR) of wheat change modelled carbon accumulation? Removal of straw from arable soil for energy provision will gain more attention. Default SGR of the selected carbon model underestimates biomass input to soil by ∼47%. Consequently carbon accumulation is underestimated by up to 24%.